ANXIOLYTIC EFFECT OF COUROUPITA GUIANENSISAUBL. FLOWER EXTRACTS IN MICE - VINOD H. GUPTA; SHAIJESH S. WANKHEDE; VISHAL S. DESHMUKH; ARCHANA R. JUVEKAR (International Journal of Pharma and Bio Sciences, 2013)
Despite the traditional use of Couroupita guianensis (CG) to treat various ailments, it had been less exploited from ethnopharmacological perspective. The aim of the present study was to evaluate aqueous and methanolic extract of CG for its anxiolytic activity in mice.Swiss albino male mice were orally administered both aqueous and methanolic extracts of CG at the dose of 100, 250 and 500 mg/kg/ml for 14 days. The elevated plus maze (EPM), light and dark (LD), and Open field test (OFT) models were used to evaluate the anxiolytic activity. Both the aqueous and methanolic extracts of CG at a dose of 500 mg/kg significantly showed an anxiolytic activity compared to vehicle control in EPM, LD, and OFT model in mice. This is the first reported study of CG flower extracts for its anxiolytic potential activity. Further study needs to be performed for isolating the active constituent to prove mechanism based activity.